Normalisasi Tekanan Akademik dalam Tinjauan Psikologi Terhadap Budaya Prestasi - Eva Fitriyani; Ellen Prima (CV. Rumoh Aceh Publishing, 2026)
This study aims to examine the normalization of academic pressure on achievement culture from the perspective of educational psychology and its impact on student well-being. In today's education system, academic pressure is often considered normal and a driving force for student achievement. The method used in this study is a qualitative approach, conducted through literature review, utilizing various sources, such as books, journals, and other scientific documents, which were analyzed descriptively to gain a deeper understanding. The analysis results indicate that academic pressure is often perceived as part of the learning process and is considered a guide to success. However, this normalization can have numerous negative impacts, such as increased stress, anxiety, mental fatigue, and decreased motivation in individual students. Furthermore, in the modern era, the education system focuses more on outcomes than on the learning process. Therefore, a more humane, supportive, and student-centered educational approach is urgently needed, balancing academic achievement with psychological well-being.